2012 IEEE-EMBS Conference on Biomedical Engineering and Sciences 2012
DOI: 10.1109/iecbes.2012.6498185
|View full text |Cite
|
Sign up to set email alerts
|

Innovative telemedicine solutions for diabetic patients

Abstract: The purpose of this paper is to highlight the best practices in development of telemedicine services for selfmanagement of patients with diabetes. Target group consisted of type 1 patients of age 27-38. These practices are derived from authors experience, patients and physicians involvement, literature and existing solutions review. Developed mHealth telemedicine system is introduced. Results on usability and acceptability of the proposed solution are described from field testing and patients' feedback. Discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Most apps in this category transmitted entered data to a server where it was available for healthcare providers to accordingly provide feedback via phone calls, text messages, or visiting the patients. For instance, diabetes apps such as WellDoc [ 15 , 42 ], Bant [ 43 ], Patient’s Mobile Unit (PMU) [ 44 ], Diabetes Assistant (DiAs) [ 45 ], Glucose Buddy [ 46 ], t+ Diabetes [ 47 ], DIABTel [ 48 ], Diab-Memory [ 49 ], Well-Mate [ 50 ], and t+ Medical [ 51 ] allowed patients to enter their glucometer readings into a smartphone or a PDA, and sent them to the healthcare provider for follow-up and personalized feedback. HbA1c was measured in seven studies, only one of which did not manage to achieve improvement [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most apps in this category transmitted entered data to a server where it was available for healthcare providers to accordingly provide feedback via phone calls, text messages, or visiting the patients. For instance, diabetes apps such as WellDoc [ 15 , 42 ], Bant [ 43 ], Patient’s Mobile Unit (PMU) [ 44 ], Diabetes Assistant (DiAs) [ 45 ], Glucose Buddy [ 46 ], t+ Diabetes [ 47 ], DIABTel [ 48 ], Diab-Memory [ 49 ], Well-Mate [ 50 ], and t+ Medical [ 51 ] allowed patients to enter their glucometer readings into a smartphone or a PDA, and sent them to the healthcare provider for follow-up and personalized feedback. HbA1c was measured in seven studies, only one of which did not manage to achieve improvement [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…HbA1c was measured in seven studies, only one of which did not manage to achieve improvement [ 50 ]. Other studies indicated a reduced rate of emergency department visits and hospitalizations [ 15 ], an increase in the average daily frequency of blood glucose measurement [ 43 ], an increase in patient confidence [ 44 ], and a decrease in the duration of hypoglycemic events [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on our analysis we found interesting results concerning other types of chronic diseases, such as diabetes, which is mentioned in 18 of our 106 papers. Together with cancer, stroke, and chronic obstructive pulmonary disease (COPD), diabetes is on the list of the major chronic diseases responsible for more than 60% of deaths in the world [ 51 ]. The mobile device is the main technology adopted but text messaging and remote monitoring devices are also used.…”
Section: Resultsmentioning
confidence: 99%
“…). As reported in[3] patients generally preferred to use their own mobile phones. Mobile terminal provided in this study (GSmart Roma R2 with OS Android 4.4.2) had two SIM slots and patients could use their own SIM card in addition to one with data package provided by the R&D team.Healthcare provider unit (HPU): web application enables healthcare professionals to overview and manage evolution of patient's health based on data from telemonitoring, modify treatments and communicate through text messages with patients.…”
mentioning
confidence: 83%